PATH-34. GENETIC PROFILING OF AGGRESSIVE MENINGIOMAS REVEAL DIVERSE SPECTRUM OF ACCOMPANYING ALTERATIONS BEYOND NF2 INACTIVATION. (9th November 2020) - Schulte, Jessica; Magill, Stephen; Nguyen, Minh; Bush, Nancy Ann Oberheim; Villanueva-Meyer, Javier; Theodosopoulos, Philip; McDermott, Michael; Butowski, Nicholas; Bollen, Andrew; Tihan, Tarik; Lee, Julieann; Pekmezci, Melike; et al.
Abstract: BACKGROUND: Meningiomas are the most common primary central nervous system tumor in adults. The majority are clinically indolent and WHO grade I. However, 20-30% are WHO grade II and 1-3% are WHO grade III, which have shorter progression-free (PFS) and overall survival. A subset of grade I meningiomas also follow an aggressive course, requiring serial resection and/or radiotherapy, similar to high-grade meningiomas. The objective of this study was to characterize the genetic alterations in meningiomas with an aggressive clinical course. METHODS: Targeted next-generation sequencing (NGS) of 40 aggressive meningiomas was performed using the UCSF500 cancer panel, which assesses ~500 cancer-related genes. Information on patient demographics, tumor histopathology, and treatment history was also collected. RESULTS: Meningiomas analyzed included 15 (38%) WHO grade I, 11 (28%) WHO grade II, and 13 (33%) WHO grade III. At the time of genetic profiling, 71% of patients had received prior treatment (68% surgery, 48% fractionated radiotherapy, 23% radiosurgery). The most commonly altered gene was NF2, with 71% of tumors demonstrating biallelic inactivation. Other common alterations included biallelic CDKN2A/B deletion (15%) and TERT amplification or promoter mutation (13%). Other recurrent alterations involved SUFU (8%), and ARID1A, ATM, BAP1, DMD, KDM6A, and PTEN (each 5%). Genes which are commonly altered in indolent WHO grade I meningiomas, such as AKT1, KLF4, PIK3CA, SMO, and TRAF7, were intact in this cohort. CONCLUSIONS: The additional genetic alterations beyond NF2 inactivation that drive aggressive meningiomas are diverse and include homozygous deletion of CDKN2A (negative regulator of cyclin-dependent kinases 4/6), inactivating mutations in SUFU (a negative regulator of Hedgehog signaling), homozygous deletion of PTEN (a negative regulator of mTOR signaling), and mutations/deletions in epigenetic regulatory factors (e.g. ARID1A, KDM6A ). Clinical trials are needed to assess the efficacy of therapeutics targeting these specific pathways in patients with meningiomas refractory to conventional treatments.